The numerical distribution of some British breeding - Yarker, Barbara; Atkinson-Willes, G L (Wildfowl, 1971)
Between 1965 and 1970 the Wildfowl Trust organised an investigation into the numbers and distribution of wildfowl breeding in Britain. During part of this period the British Trust for Ornithology has also been conducting a survey of the breeding distribution of British birds, though not on a quantitative basis. Although the latter is unfinished, the data obtained up to 15th March 1971 have been made available for inclusion in the present paper. Maps to show the number of pairs breeding in each 10 km. square of the National Grid have been compiled for Wigeon Anas penelope, Shoveler A. clypeata, Tufted Duck Aythya fuligula, Pochard A. ferina and Shelduck Tadorna tadorna. These are accompanied by estimates of total population, and a rsum of recent changes.